Peran dan Fungsi Kedudukan Sarak Opat dalam Sistem Pemerintahan Di Kampung - Maifa Fitri (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2023)
Sarak Opat as a customary institution is authorized to resolve, investigate and impose customary sanctions based on customary law and customs against sumang (discordant) actions, and violating customs committed by a person. This also applies in Waq Pondok Sayur village, Bukit sub-district, Bener Meriah district. The function and role of sarak opat in its implementation is not well implemented where in cases of customary violations that occur, the perpetrators do not carry out and carry out as customary sanctions. This article is studied using empirical juridical research methods. As for the results of the research obtained, the role and function of the position of Sarak Opat in Waq Pondok Sayur village in handling customary cases that occur is less effective and less in accordance with what is expected by the community. The obstacles faced by Sarak Opat in carrying out its functions and roles are due to the absence of a written qanun in the village regarding the existence of Parak and paying fines to anyone who commits customary violations. In addition, Sarak Opat has not properly understood their respective functions and roles, thus causing an unfavorable impact on the Waq Pondok Sayur village.